Emerging roles of long non-coding RNA in root developmental plasticity and regulation of phosphate homeostasis - Bazin, Jeremie; Bailey-Serres, Julia (Frontiers in Plant Science, 2015)
Long non-coding RNAs (lncRNAs) have emerged as important regulators of gene expression in a variety of biological process and in multiple species. In plants, they are transcribed by different RNA polymerases and show diverse structural features. With the aid of next-generation sequencing technologies, a large number of lncRNA have been identified in model plants as well as in crops. This review focuses on the demonstration that lncRNAs control root system architecture, notably in response to phosphate availability, through regulation of transcription, alternative splicing, microRNA activity, messenger RNA stability and translation, illustrating remarkable diversity in their roles in regulating developmental plasticity.